Sindicalismo e desenvolvimento rural: a construção do acesso às políticas públicas pela agricultura familiar de são lourenço do oeste - sc - Simonetti, André Luiz (2025)
Since 1970, the family farming union of São Lourenço do Oeste, in Santa Catarina, has been the main representative entity of the category. The aim here is to analyze the role of unionism in promoting and accessing local rural development public policies. For this purpose, interviews were conducted with former union presidents and associates between 2021 and 2022, as well as a documentary analysis of the minutes of board meetings and general assemblies held since its foundation. Records and testimonies were found that revealed actions by the union to build public policies for health care and social security, rural credit, and improvements in the working and production conditions of farming families, and in a more recent period, also involvement in seeking housing policies and increasing and diversifying income opportunities through access to institutional markets. All actions that have improved the quality of life of farming families.